2006
DOI: 10.1002/chem.200600699
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Base‐Pair‐Specific Optical Properties of the DNA Stain Thiazole Orange

Abstract: Double‐stranded DNA offers multiple binding sites to DNA stains. Measurements of noncovalently bound dye–nucleic acid complexes are, necessarily, measurements of an ensemble of chromophores. Thus, it is difficult to assign fluorescence properties to base‐pair‐specific binding modes of cyanine dyes or, vice versa, to obtain information about the local environment of cyanines in nucleic acids by using optical spectroscopy. The feasibility to stain DNA and simultaneously probe local perturbations by optical spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
80
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 50 publications
6
80
0
4
Order By: Relevance
“…[29][30][31] YO and TO have also been covalently linked to oligonucleotides and inserted into peptide nucleic acids constructs, which become fluorescent upon hybridisation of the light-up probe to a specific complementary strand. [32][33][34][35][36][37][38] The origin of the very high contrast in emission between the free and the bound form of the dyes has long been thought to be due to an ultrafast decay of the excited state of the free form through a large-amplitude torsional motion around the monomethine bond connecting the benzoxazole, benzothiazole and quinoline moieties, respectively. [39,40] This isomerisation mechanism is blocked upon intercalation of the dyes into DNA and, as a consequence, they light-up by three orders of magnitude.…”
mentioning
confidence: 99%
“…[29][30][31] YO and TO have also been covalently linked to oligonucleotides and inserted into peptide nucleic acids constructs, which become fluorescent upon hybridisation of the light-up probe to a specific complementary strand. [32][33][34][35][36][37][38] The origin of the very high contrast in emission between the free and the bound form of the dyes has long been thought to be due to an ultrafast decay of the excited state of the free form through a large-amplitude torsional motion around the monomethine bond connecting the benzoxazole, benzothiazole and quinoline moieties, respectively. [39,40] This isomerisation mechanism is blocked upon intercalation of the dyes into DNA and, as a consequence, they light-up by three orders of magnitude.…”
mentioning
confidence: 99%
“…As a result, the brightness of TO emission is higher in the DNA–RNA duplex formed upon hybridization of FIT‐DNA than that in the PNA–RNA duplex formed with FIT‐PNA. This also is in agreement with previous studies, which have shown that the nonconjugated TO dye is a rather modest stain of PNA–DNA duplexes …”
Section: Resultsmentioning
confidence: 99%
“…The excitation wavelength of the probes was set at the absorption maximum wavelength of the TO unit in the absence of target siRNAs. Fluorescence quantum yield ( Φ ) was determined relative to fluorescein, for which the probe in free or siGL2‐bound states was examined ([probe]=200 n m , [siGL2]=2.0 μ m ).…”
Section: Methodsmentioning
confidence: 99%